Gestión financiera y su incidencia en la administración de las cuentas por cobrar de la junta de agua potable y alcantarillado santa maría del toachi, año 2021 - Campoverde Ponce , Daysi Carolina (2024)
The objective of this investigation is to evaluate financial management and its impact on the accounts receivable of the Santa Maria del Toachi Drinking Water and Sewerage Board, of the Santo Domingo canton. Financial management is a tool in which you can control and supervise the income and expenses of the organization. In this organization you can observe the high number of partners pending payment for the service offered, the lack of trained personnel to carry out the Control of collections and late payment for services offered affects correct decision-making. The universe of the investigation was the accounts receivable, where a review of these accounts was carried out, in the organization there is a deficiency, since the accounts receivable are not recorded in an accounting system, but in physical sheets so which is difficult to know the value they owe to the Santa Maria del Toachi Drinking Water and Sewerage Board. Interviews were carried out with Administrative Personnel to find out the shortcomings they have in accounting matters; and member surveys. The documents where control of payments was kept were reviewed.